Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian Moisturizer Originote di Kalangan Gen Z Kota Jambi - Putri Nadia Isnaini; Sigit Indrawijaya; Husni Hasbullah (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to analyze the influence of product quality and price on the purchase decision of Originote moisturizer among Gen Z Jambi City. The independent variables in this study are product quality and price, while the dependent variable is the purchase decision. The research method used is quantitative with the type of associative research. Data was collected through a questionnaire distributed to 97 respondents who are Gen Z in Jambi City. Data analysis using multiple linear regression. Research results show that product quality and price simultaneously have a significant effect on the purchase decision of Originote moisturizer. Partially, product quality has a positive and significant effect on purchasing decisions, and price also has a positive and significant effect on purchasing decisions. Variations in purchasing decisions can be explained by product quality and price.